2017
DOI: 10.1111/famp.12330
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Attunement Moderates the Prospective Link between Parental Overcontrol and Adolescent Adjustment

Abstract: Parental overcontrol (OC), behavior that intrusively or dominantly restricts child autonomy, has been identified as a transdiagnostic risk factor for youth. However, it is as yet unknown whether the association between parental OC and child maladjustment remains even when OC is exerted infrequently or by attuned parents. Rather, the selective use of OC might steer children away from danger. Taking a developmental psychopathology approach, this study focuses on the larger parent-child relationship context, test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…However, our effect sizes could be used to inform predictions and power considerations in future longitudinal studies on the curvilinear effects of normative family stressors. In addition, the obtained effect sizes were rather modest, as may be expected when testing the effect of common family stressors in normative mother-child dyads and in accordance with prior studies on similar constructs e.g., (Miller et al, 2018). In addition, mothers reported on global PS and not specifically their PS related to the participating children; thus, we cannot rule out the possibility that children’s symptom level was indirectly affected by maternal parenting stress related to siblings (Dirks, Persram, Recchia, & Howe, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, our effect sizes could be used to inform predictions and power considerations in future longitudinal studies on the curvilinear effects of normative family stressors. In addition, the obtained effect sizes were rather modest, as may be expected when testing the effect of common family stressors in normative mother-child dyads and in accordance with prior studies on similar constructs e.g., (Miller et al, 2018). In addition, mothers reported on global PS and not specifically their PS related to the participating children; thus, we cannot rule out the possibility that children’s symptom level was indirectly affected by maternal parenting stress related to siblings (Dirks, Persram, Recchia, & Howe, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The handful of studies examining maternal attunement among older children has focused on children' perception of maternal attunement. For example, in a study of midadolescents, child-reported maternal attunement buffered the detrimental effects of observed parental overcontrolling on children's internalizing symptoms (Miller, Borelli, & Margolin, 2018).…”
Section: Maternal Attunement As a Moderatormentioning
confidence: 99%
See 1 more Smart Citation
“…We coded mothers’ OC from the video‐recorded PCT using the Behavioral Involvement Parenting Scale (BIPS; Rasmussen & Borelli, ), a scale modeled after the Nursing Child Assessment Satellite Training Teaching Scales (NCAST; Barnard & Eyres, ), a common coding system used to assess parent–child interactions. The BIPS was developed as a measure of parental OC and support using definitions of these constructs within the literature and after consulting other coding systems and parenting experts regarding these constructs (Barber, ; Bögels & Brechman‐Toussaint, ; Grusec & Davidov, ; Miller, Borelli, & Margolin, ). The BIPS was specifically developed to be appropriate for assessing parental OC and support in the context of the PCT, and therefore seeks to capture the full range of parenting behaviors exhibited in this task.…”
Section: Methodsmentioning
confidence: 99%
“…63 Attunement Attunement between parent and child is the ability to perceive and respond appropriately to the thoughts, feelings and behaviours of the child and to adapt to the needs of the child (Di Renzo et al, 2020). 64 Attunement may be essential for sensitive parenting (Miller et al, 2018). 65 Parental sensitivity…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%